The Application of Empty Palm Fruit Bunch (EPFB) As A Material for Fixed Wing Type Unmanned Aerial Vehicle Fuselage Production - Muhammad Teguh Teguh; Kaspul Anuar; Muhammad Taslim; Rexy Guruh Saputra (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2019)
One of a potential application of Empty Palm Fruit Bunch (EPFB) is the material of fuselage on Unmanned Aerial Vehicle (UAV). This study was began by Alkali Treatment on EPFB. Then, the fuselage was molded using Vacuum Bagging Method. There are three unit of mold with combination of fiberglass + carbon fiber, fiberglass + EPFB fiber and full EPFB fiber. The measurement show fuselage with hybrid composite material (fiberglass and EPFB) has the lightest mass of 559 gram. Deflection Test of all three fuselages show that the maximum deflections were under 1 mm. Next, the Static Impact Test show no damages or cracks on all three fuselages. The result of Flight Test show all fuselages could do well fly and survive belly landing.